NILAI PENDIDIKAN KARAKTER CERPEN LUH AYU MANIK MAS NGALAHANG LEGU POLENG KARYA SUHENDRI YANI DAN MELANIA TORREY - Ni Made Yuni Suarsini; A.A. Made Putra Arsana (Kalangwan Jurnal Pendidikan Agama, Bahasa dan Sastra, 2022)
One of the modern Balinese literary works that has developed in the community is the short story Luh Ayu Manik Mas Ngalahang Legu Poléng. The short story contains the value of good education to shape the character of the community. Likewise, the contents of the short story are very closely related to people's lives today. So that it is more interesting to know the values ​​of the short stories, especially the character values ​​of the characters. Based on the thoughts above, this study will discuss the problem, namely the value of character education contained in the short story of Luh Ayu Manik Mas Ngalahang Legu Poléng. Keywords: Short story of Luh Ayu Manik Mas Ngalahang Legu Poléng, and the value of character education.